Numerical simulation of hypersonic flow around semi-sphere with non-equilibrium physical and chemical processes in high-temperature air - Volkov, Konstantin N.; Gimadiev, Vladislav A.; Dobrov, Yuri V.; Karpenko, Anton G. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2022)
High-temperature effects have a significant impact on the characteristics of aircraft moving at hypersonic speed. Due to the complexity of setting up a physical experiment, mathematical modelling plays an important role in finding the characteristics of hypersonic aircraft. The construction and implementation of a mathematical model for the numerical simulation of a hypersonic flow around a semi-sphere is discussed, taking into account non-equilibrium physical and chemical processes in high-temperature air. The mathematical model includes the equations of gas dynamics, the equations of the turbulence model and the equations of chemical kinetics. Numerical simulation of supersonic and hypersonic air flow around a hemi-sphere is carried out, taking into account high-temperature effects. A critical review of various models that are used to find the shock stand-off is given. The results of calculations obtained using the developed numerical method are compared with the data of a physical experiment and the computational data available in the literature in a wide range of Mach numbers. The developed model and computational results are important for simulation of flows around bodies of complex configuration and designing high-speed aircraft.